See think act: the need to rethink and refocus on relational security. Issue 2 (4th March 2022) - Markham, Sarah
ABSTRACT: In this paper, we present an account of the nature of relational security and the need for robust, comprehensive and consistent implementation within secure and forensic mental health settings in England and Wales. Within this, we review and critique the See Think Act framework of relational security and consider how it may be further developed. We conclude by making a series of evidence-based recommendations for improving the quality of relational security as it is deployed within secure and forensic mental health settings.